2005
DOI: 10.1111/j.1460-9568.2005.03930.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatodendritic autoreceptor regulation of serotonergic neurons: dependence on l‐tryptophan and tryptophan hydroxylase‐activating kinases

Abstract: The somatodendritic 5-HT(1A) autoreceptor has been considered a major determinant of the output of the serotonin (5-HT) neuronal system. However, recent studies in brain slices from the dorsal raphe nucleus have questioned the relevance of 5-HT autoinhibition under physiological conditions. In the present study, we found that the difficulty in demonstrating 5-HT tonic autoinhibition in slice results from in vitro conditions that are unfavorable for sustaining 5-HT synthesis. Robust, tonic 5-HT(1A) autoinhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 64 publications
(93 reference statements)
7
46
0
Order By: Relevance
“…However, other studies failed to con- firm this and suggested that some other 5-HT receptor subtype contributes (Moret and Briley, 1997;Stenfors et al, 2001). Interestingly, TRP and the activation of TPH by Ca/calmodulin kinase II and protein kinase A enhanced 5-HT 1A receptor-mediated inhibition of dorsal raphe 5-HT neurons (Liu et al, 2005). Thus, autoreceptor-mediated inhibition of brain 5-HT synthesis is quite likely impaired in DBA/2J and BALB/c mice.…”
Section: Discussionmentioning
confidence: 92%
“…However, other studies failed to con- firm this and suggested that some other 5-HT receptor subtype contributes (Moret and Briley, 1997;Stenfors et al, 2001). Interestingly, TRP and the activation of TPH by Ca/calmodulin kinase II and protein kinase A enhanced 5-HT 1A receptor-mediated inhibition of dorsal raphe 5-HT neurons (Liu et al, 2005). Thus, autoreceptor-mediated inhibition of brain 5-HT synthesis is quite likely impaired in DBA/2J and BALB/c mice.…”
Section: Discussionmentioning
confidence: 92%
“…In our experiments, 89% (n ϭ 196) of the cells displayed the characteristic electrophysiological profile of 5-HT neurons. The vast majority of these cells fired spontaneously at the onset of recordings, unless slices were exposed to tryptophan prior to recording (Liu et al 2005) (n ϭ 15, not shown). In that case, DRN neurons secrete 5-HT within the nucleus, which hyperpolarizes DRN neurons and reduce spontaneous activity (Johnson et al 2002;Liu et al 2005).…”
Section: R E S U L T Smentioning
confidence: 99%
“…The vast majority of these cells fired spontaneously at the onset of recordings, unless slices were exposed to tryptophan prior to recording (Liu et al 2005) (n ϭ 15, not shown). In that case, DRN neurons secrete 5-HT within the nucleus, which hyperpolarizes DRN neurons and reduce spontaneous activity (Johnson et al 2002;Liu et al 2005). In the absence of the 5-HT precursor tryptophan, endogenous paracrine 5-HT release is low or absent in DRN slices (Johnson et al 2002), providing a good starting point for quantitative measures of the exogenous 5-HT-induced GIRK responses.…”
Section: R E S U L T Smentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that αCaMKII phosphorylates a wide variety of substrates involved in numerous neuronal processes (McGlade-McCulloh, 1993;Omkumar, 1996;Stefani, 1997;Liu, 2005) and we have identified ERK1/2, CREB, and MAP2 as proteins targeted by E2-induced αCaMKII autophosphorylation in NLT and primary hippocampal neurons. Like αCaMKII, all three proteins are involved in neuronal differentiation, and ERK1/2 and CREB have also been shown to play a role in LTP and memory processes (Trifilieff, 2006).…”
Section: Discussionmentioning
confidence: 81%